2023
DOI: 10.1186/s12872-023-03146-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of myocardial bridging and the pericoronary fat attenuation index on coronary computed tomography angiography: predicting coronary artery disease risk

Abstract: Background The fat attenuation index (FAI) is a radiological parameter that represents pericoronary adipose tissue (PCAT) inflammation, along with myocardial bridging (MB), which leads to pathological shear stress in the coronary vessels; both are associated with coronary atherosclerosis. In the present study, we assessed the predictive value of FAI values and MB parameters through coronary computed tomography angiography (CCTA) for predicting the risk of coronary atherosclerosis and vulnerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…While Matta et al 33 and Darabant et al 21 find the presence of MB to be associated with atherosclerotic risk reduction and even protective in a 10-year follow-up, respectively, McLaughlin et al 30 and Lu et al 31 independently showed MB-linked atherosclerosis to be mediated via complex adipogenesis and angiogenesis-mediated mechanisms. The prevalent finding of proximal to MB atherosclerosis is confirmed by numerous authors, 6,14,19,[34][35][36] confirming different long-term influences on outcomes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While Matta et al 33 and Darabant et al 21 find the presence of MB to be associated with atherosclerotic risk reduction and even protective in a 10-year follow-up, respectively, McLaughlin et al 30 and Lu et al 31 independently showed MB-linked atherosclerosis to be mediated via complex adipogenesis and angiogenesis-mediated mechanisms. The prevalent finding of proximal to MB atherosclerosis is confirmed by numerous authors, 6,14,19,[34][35][36] confirming different long-term influences on outcomes.…”
mentioning
confidence: 99%
“…Enquanto Matta et al, 33 e Darabant et al, 21 consideram a presença de PM associada à redução do risco aterosclerótico e até mesmo protetora em seguimento de 10 anos, respectivamente, McLaughlin et al, 30 e Lu et al, 31 mostraram independentemente que a aterosclerose ligada à PM é mediada por mecanismos complexos mediados por adipogênese e angiogênese. O achado prevalente de aterosclerose proximal a PM é confirmado por numerosos autores, 6 , 14 , 19 , 34 - 36 confirmando diferentes influências de longo prazo nos resultados.…”
unclassified
See 1 more Smart Citation